[ 0,(3) + 1,(3) : 1 ] : (1+ )
Răspunsuri la întrebare
Răspuns de
1
[ 0,(3) + 1,(3) : 1 7/9] : (1+1/12 )=
= [ 3/9 + (13-1)/9 : 16/9] : (12+1)/12=
= ( 1/3 + 12/9 × 9/16) : 13/12=
= ( 1/3 + 12/16) × 12/13=
= ( 1/3 + 3/4) × 12/13=
= ( 4+9)/12 × 12/13=
=13/12× 12/13=1
= [ 3/9 + (13-1)/9 : 16/9] : (12+1)/12=
= ( 1/3 + 12/9 × 9/16) : 13/12=
= ( 1/3 + 12/16) × 12/13=
= ( 1/3 + 3/4) × 12/13=
= ( 4+9)/12 × 12/13=
=13/12× 12/13=1
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Chimie,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă